Numerical Crashworthiness Analysis of Graded Layered Foam- Filled Tubes Under Axial Loading - Payman Ghazifard; Amir Najibi; Parisa Alizadeh (Mechanics of Advanced Composite Structures)
In this article, the results of a study on energy absorption characteristics of foam-filled thin-walled structures with finite element analysis have been presented. Four specimens of thin walled structures have been filled with uniform foam and three specimens have been filled with linear four-layered foam. Also, eight layers HLH (High-Low-High) and eight layers LHL (Low-High-Low) have been simulated. The total weight of all layered specimens is the same and main difference is just the arrangement of the layers. In order to study the energy absorption behavior of the specimens, they have been subjected to quasi-static crushing load. The results indicated that by utilizing the filler foam in the thin-walled energy absorbers, the energy absorption capacity of the foam filled specimens in comparison with hollow specimens, significantly promotes; however, the initial peak force for hollow specimens is lower than the foam-filled specimens. Consequently,  from the layered specimens, LHL showed higher specific energy absorption and less initial peak force compared with other specimens, in which the LHL specimen shows 16% more initial peak force and 114% more specific energy absorption than the hollow specimen.